DEVELOPMENT OF CAREER INFORMATION MEDIA FOR HIGH SCHOOL STUDENTS IN JAKARTA - Farawowan, Fauziah F; Subroto, Desty Endrawati; Sujatmiko, Wandi; Assabana, Mohammad Syahru; Nastiti, Arum Eki (Jurnal Kajian Pendidikan dan Psikologi, 2023)
The goal will be achieved in the study. This is about developing career information media for public high school students in Jakarta. Research conducted uses approach research and development. Type study This is used based on an objective study, i.e., it produces a product form for planning media careers for state high school students in Jakarta who meet criteria for acceptability. The results of this research, namely the average calculation of all percentage scores obtained from the design validation stage, which involved assessments from material experts, media experts, guidance and counselling teachers, and students, found that the average score reached 93%. This value is included in the very good criteria, so no revision is needed. Therefore, it can be concluded that the roadmap media product has met the acceptability criteria, which cover the aspects of usability, feasibility, appropriateness, and accuracy very well, so it does not need to be revised.